Nucleation of water clusters on functionalised graphite with kinetic Monte Carlo scheme. Issue 13 (2nd September 2022) - Tan, Shiliang (Johnathan); Do, D. D.; Chew, Jia Wei
ABSTRACT: Although activated carbon is generally hydrophobic, water can adsorb on its surface due to the presence of functional groups. During the initial interactions between functional groups and water molecules, atoms of the functional groups rotate around the sigma bonds to maximise the electrostatic interactions. This physical process was simulated within the framework of kinetic Monte Carlo (kMC). We extended kMC to account for the rotation of the atoms of functional groups around the sigma bonds by entropic sampling of the orientation space, and tested the modified kMC scheme for adsorption of water on graphite functionalised with either hydroxyl groups or carboxyl groups. Results show that the amount adsorbed is greater when the rotation of atoms around the sigma bonds is allowed. The interspacing of functional groups also affects the adsorbed density. It was found that the optimum distances between hydroxyl groups and carboxyl groups to initiate water cluster are 0.4 and 0.7 nm, respectively, because of the synergistic effect of electrostatic interactions between water molecule and adjacent functional groups. This effect is reduced when the spatial distance is either decreased (because of the increasing importance of the repulsion) or increased (because of the loss of the synergetic effect).